MOLECULAR DYNAMICS STUDY OF HAEMOGLOBIN COMPLEXED WITH HYPEROSIDE - M. UMA MAKHESWARI; D. SUDARSANAM (International Journal of Pharma and Bio Sciences, 2013)
Diabetes mellitus type 2 (formerly noninsulin-dependent diabetes mellitus (NIDDM) or adult onset diabetes) is a metabolic disorder that is characterized by high blood glucose either due to insulin resistance or insulin deficiency. Using bio-informatics, human hemoglobin was targeted for docking a ligand at pre-specified regions of its three dimensional structure for Type 2 Diabetes mellitus. Wide ligand search from databases identified hyperoside as desirable ligands that docked well with protein haemoglobin. Molecular dynamics simulations were made to study the drugs-protein interactions. It was shown that RMSD (Root Mean Square Deviation) curve for haemoglobin-hyperoside complex are remarkably more stable. The results demonstrate that hyperoside might be potentially used for blood glucose regulation.